Modern education; problems and prospects for further development - Smirnov S. N., Lavina T. A., Gritskevich T. I., Zakharova A. N., Golovina A. G., Larina E. A., Chernyshev V. P., Timoshkov E. V. (Modern education; problems and prospects for further development, 2019)
the article deals with the questions of organization of work with gifted students in the space of higher educational institutions of the Russian Federation. Activity on educational support of talented and highly motivated pupils of some leading universities of Russia is considered. The author emphasizes that in order to ensure the optimal functioning of the mechanism for creating a model of general education in the space of a modern university, it is necessary to take measures to improve the legal framework.
Keywords: общее образование; система высшего образования; профориентационная работа; одаренные обучающиеся; углубленная подготовка; gifted students; higher education system; general education; advanced training; vocational guidance work